Preclinical Efficacy of Pro- and Anti-Angiogenic Peptide Hydrogels to Treat Age-Related Macular Degeneration - Amanda Acevedo-Jake; Siyu Shi; Zain Siddiqui; Sreya Sanyal; Rebecca Schur; Simon Kaja; Alex Yuan; Vivek A. Kumar (Bioengineering, 2021)
Pro-angiogenic and anti-angiogenic peptide hydrogels were evaluated against the standard of care wet age-related macular degeneration (AMD) therapy, Aflibercept (Eylea®). AMD was modeled in rats (laser-induced choroidal neovascularization (CNV) model), where the contralateral eye served as the control. After administration of therapeutics, vasculature was monitored for 14 days to evaluate leakiness. Rats were treated with either a low or high concentration of anti-angiogenic peptide hydrogel (0.02 wt% 8 rats, 0.2 wt% 6 rats), or a pro-angiogenic peptide hydrogel (1.0 wt% 7 rats). As controls, six rats were treated with commercially available Aflibercept and six with sucrose solution (vehicle control). Post lasering, efficacy was determined over 14 days via fluorescein angiography (FA) and spectral-domain optical coherence tomography (SD-OCT). Before and after treatment, the average areas of vascular leak per lesion were evaluated as well as the overall vessel leakiness. Unexpectedly, treatment with pro-angiogenic peptide hydrogel showed significant, immediate improvement in reducing vascular leak; in the short term, the pro-angiogenic peptide performed better than anti-angiogenic peptide hydrogel and was comparable to Aflibercept. After 14 days, both the pro-angiogenic and anti-angiogenic peptide hydrogels show a trend of improvement, comparable to Aflibercept. Based on our results, both anti-angiogenic and pro-angiogenic peptide hydrogels may prove good therapeutics in the future to treat wet AMD over a longer-term treatment period.